2009
DOI: 10.1902/jop.2009.080568
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Residual Bone on Recombinant Human Bone Morphogenetic Protein‐2–Induced Periodontal Regeneration in Experimental Periodontitis in Dogs

Abstract: The width of residual bone was one of the clinical host factors that affected bone regeneration following BMP implantation. However, it did not affect connective tissue attachment, cementum regeneration, and downgrowth of junctional epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…The basic components for tissue engineering involve an interactive triad of scaffolds [79][80][81] , signaling molecules [82][83][84] and cells [24,33,41,85] , which play a fundamental role in the regeneration process [24,76,86,87] . Scaffolds serve as a threedimensional template mimicking the extracellular matrix; signaling molecules enhance this cellular activity by stimulating cells to migrate, proliferate and differentiate; and cells provide the machinery synthesis of the extracellular matrix and tissue regeneration [24,75,76,88,89] .…”
Section: Perspectives On Tdscs In Regenerative Approachesmentioning
confidence: 99%
“…The basic components for tissue engineering involve an interactive triad of scaffolds [79][80][81] , signaling molecules [82][83][84] and cells [24,33,41,85] , which play a fundamental role in the regeneration process [24,76,86,87] . Scaffolds serve as a threedimensional template mimicking the extracellular matrix; signaling molecules enhance this cellular activity by stimulating cells to migrate, proliferate and differentiate; and cells provide the machinery synthesis of the extracellular matrix and tissue regeneration [24,75,76,88,89] .…”
Section: Perspectives On Tdscs In Regenerative Approachesmentioning
confidence: 99%
“…A drug delivery system by means of a combination of polymers and GFs, in many cases, can provide a well-controlled release of its cargo into a local microenvironment to yield desirable concentrations over a period ranging from days to months. Frequently used polymers for the delivery of bioactive factors, particularly for periodontal regeneration, include synthetic materials such as polyglycolic acid (PGA), polylactic acid (PLA) and their copolymers (PLGA) [38e40]; beta-tricalcium phosphate (beta-TCP) [41,42]; and natural polymers such as dextran [43], gelatin [39,44], and collagen [45,46]. There is evidence that a combination of several materials may offer the best opportunity for beneficial clinical outcomes.…”
Section: Localized Delivery Of Growth Factors For Periodontal Regenermentioning
confidence: 99%
“…[4] Recent studies have utilized recombinant human BMP to determine their potential for correcting intrabony, supra-alveolar, furcation, and fenestration defects. [20] However, in most of these studies, histologic analysis has revealed periodontal regeneration with areas of ankylosis. Contrary to these findings, BMP-7 augmentation resulted in a significant increase in periodontal regeneration without any ankylosis; so most of the recent research utilizing recombinant human BMP-7 has been involved in the preparation of implant site for ossteointeration.…”
Section: Factors Affecting Bone Morphogenetic Proteins Activitymentioning
confidence: 99%